Stress Distribution after Installation of Fixed Frameworks with Marginal Gaps over Angled and Parallel Implants: A Photoelastic Analysis - Roberto Adrian Markarian, DDS;1 Cristiane Ueda, DDS;1 (Journal of Prosthodontics, 2007)
The objective of this work was to compare by photoelastic analysis the stress distribution along a fixed framework placed over angled or parallel implants with different gap values between the framework and one of the implants